2002
DOI: 10.3354/meps240225
|View full text |Cite
|
Sign up to set email alerts
|

Risk of collapse in the eastern Baltic cod fishery

Abstract: The eastern Baltic cod fishery, as many fisheries worldwide, is experiencing a major crisis. The combination of current environmental conditions, fishing mortality rates, and stock size indicates that this fishery is not sustainable. In order to rebuild the population and sustain the fishery in the future, it is essential to define a biologically appropriate exploitation level. In this paper, we take a decision-theoretical approach and use risk analysis to compare different management actions in terms of fishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 42 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…The coalescence‐based simulations showed that around 30 lineages (alleles) could still be present after a severe bottleneck lasting for 10 generations or less, which was compatible both with the levels of variability and with the onset of over‐exploitation of North Sea cod (Cook et al . 1997) and Baltic Sea cod (Jonzén et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The coalescence‐based simulations showed that around 30 lineages (alleles) could still be present after a severe bottleneck lasting for 10 generations or less, which was compatible both with the levels of variability and with the onset of over‐exploitation of North Sea cod (Cook et al . 1997) and Baltic Sea cod (Jonzén et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, in some years even these adaptations are insufficient to ensure reproductive success (Köster et al , 2005). Continued high fishing pressure in combination with frequent periods of detrimental environmental conditions for egg survival suggests that this population may collapse (Jonzen et al , 2002; ICES, 2005a), as happened to the central Baltic dab and plaice stocks during the 20th century (Temming, 1989). If the eastern Baltic cod population were to collapse, then recovery would be very slow or perhaps impossible even under low or no fishing mortality.…”
Section: Fisheries Management During 21st Century Climate Changementioning
confidence: 99%
“…There have been increasing efforts to analyze the risk of collapse in fisheries (e.g., Johnston and Sutinen 1996;Myers, Hutchings, and Barrowman 1997;Hutchings 2000;Jonzén et al 2002;Escudero et al 2004;Hutchings and Reynolds 2004;Mullon, Fréon, and Cury 2005;Mitra and Roy 2006). Many scientists and managers consider fisheries collapse to be a result of purely economic or administrative mismanagement (Mullon, Fréon, and Cury 2005), and many of these studies have concentrated on overfishing as a cause of fisheries depletion and collapse.…”
Section: Introductionmentioning
confidence: 99%